The Framework of Urban Planning in China in the 21st Century: A Discipline at the service of Building a Nation (Sinología hispánica. China Studies Review, 2021)
The character of urban planning in China must be understood within the framework of the policies of the country's planning. In this context, urban planning is subordinate to the economic construction of the nation.The most eloquent image of this Post-Socialism scenario is the intense urbanization processes of cities. New residential areas, downtown and affluent business districts, industrial and technology parks, are its image. However, what is the planning framework, procedures and urban instruments that allow these processes? The political structure of the Chinese state centrallyand hierarchically directs this planning through its state policies and guidelines of the Five-Year Plans,and its sectorial implementation through the different ministries. However, a lack of integratedplanning leads to the duplicity of competencies, lack of coordination and divergence of objectives. Anew framework, the ‘duoguiheyi’, tries to alleviate this situation. The land regime and its developmentis an essential factor to understand the transformation and growth processes of cities, as well asthe entrepreneurial character of the local state. At the same time, contemporary urban planning asa discipline has a short history and a very recent legal framework that generates a lack of cases ofreference and adaptation to rapid urban dynamics. In some chapters, the city of Hangzhou will serveas an explanatory reference.